2020
DOI: 10.1016/j.chest.2019.08.2185
|View full text |Cite
|
Sign up to set email alerts
|

Estimated Ventricular Size, Asthma Severity, and Exacerbations

Abstract: BACKGROUND: Relative enlargement of the pulmonary artery (PA) on chest CT imaging is associated with respiratory exacerbations in patients with COPD or cystic fibrosis. We sought to determine whether similar findings were present in patients with asthma and whether these findings were explained by differences in ventricular size. METHODS:We measured the PA and aorta diameters in 233 individuals from the Severe Asthma Research Program III cohort. We also estimated right, left, and total epicardial cardiac ventr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…In an autopsy study by Saetta et al 9 of patients who died of asthma attacks, the peripheral pulmonary arteries adjacent to occluded and inflamed bronchioles exhibited evidence of inflammation, although none of the patients had narrowed lumens of the peripheral pulmonary arteries compared with the control group, evidence of the morphologic changes of chronic hypoxia or cor pulmonale. The authors of the current study 6 concluded that the pulmonary hypertension in COPD is likely due to parenchymal destruction and regional hypoxia, both of which are more pronounced in COPD than in asthma. This finding is supported by previous research showing that, among other risk factors, use of supplemental oxygen and a larger percentage of emphysema on CT imaging is associated with a PA/A ratio > 1 in COPD.…”
mentioning
confidence: 64%
See 4 more Smart Citations
“…In an autopsy study by Saetta et al 9 of patients who died of asthma attacks, the peripheral pulmonary arteries adjacent to occluded and inflamed bronchioles exhibited evidence of inflammation, although none of the patients had narrowed lumens of the peripheral pulmonary arteries compared with the control group, evidence of the morphologic changes of chronic hypoxia or cor pulmonale. The authors of the current study 6 concluded that the pulmonary hypertension in COPD is likely due to parenchymal destruction and regional hypoxia, both of which are more pronounced in COPD than in asthma. This finding is supported by previous research showing that, among other risk factors, use of supplemental oxygen and a larger percentage of emphysema on CT imaging is associated with a PA/A ratio > 1 in COPD.…”
mentioning
confidence: 64%
“…Perhaps more importantly, in multivariate analysis, the investigators discovered that patients with smaller ventricular volumes had increased rates of asthma exacerbations, both in the year prior to enrollment and during follow-up. These results 6 are perhaps not altogether surprising. The SARP investigators have previously reported CT imaging evidence of decreased size of the peripheral pulmonary vasculature (pruning) in patients with asthma and that this finding was correlated with a 150% increase in the odds of an asthma exacerbation.…”
mentioning
confidence: 85%
See 3 more Smart Citations